Design of Multiband Fractal Antenna - S. Nageswara Rao, B; E. Srinivasa Murthy, E (International Journal of Engineering and Technology, 2018)
Fractal is a fragmented geometry which can be segmented into various parts, each part will be the miniature copy of the whole. The main advantages of fractal antennas are its reduced size and multiband operation. These structures have self-similarity properties and fractional dimensions. The self-similar geometrical nature of fractal facilitates the antenna design to achieve multiband applications. The proposed fractal antenna can be operated in different frequencies and 2 frequency bands. The obtained frequency bands are X- band and Ku- band. The proposed antenna has been designed, simulated and analyzed by using HFSS (High Frequency Structural Simulator) software 15.0.Â Â